2021
DOI: 10.1039/d0ta11099j
|View full text |Cite|
|
Sign up to set email alerts
|

Performance optimization and fast rate capabilities of novel polymer cathode materials through balanced electronic and ionic transport

Abstract: Balancing electronic and ionic transport is crucial to developing next-generation high-power organic electrode materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…[25,[42][43][44] However, the two Pz-based polymers of BzPz and TzPz have similar surface area, indicating that the difference in rate performance of the two polymer cathodes is dominated by other factors (Figure 2c). Taking into account that the rate performance is also influenced by both the ionic and electron conductivities, [24,45,46] we first estimated the ionic diffusivities in BzPz and TzPz cathodes by galvanostatic intermittent titration technique (GITT; Figure S11, Supporting Information). The results demonstrated that the ionic diffusion efficiency in BzPz is slightly higher than that in TzPz (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[25,[42][43][44] However, the two Pz-based polymers of BzPz and TzPz have similar surface area, indicating that the difference in rate performance of the two polymer cathodes is dominated by other factors (Figure 2c). Taking into account that the rate performance is also influenced by both the ionic and electron conductivities, [24,45,46] we first estimated the ionic diffusivities in BzPz and TzPz cathodes by galvanostatic intermittent titration technique (GITT; Figure S11, Supporting Information). The results demonstrated that the ionic diffusion efficiency in BzPz is slightly higher than that in TzPz (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Abruna et al demonstrated that the ionic and electronic conductivities of the crosslinked Pz-based polymer cathodes could be balanced by tuning the length of linear polymer chains between two adjacent knots through statistical copolymerization, the optimized Pz-based polymer cathode delivered a high specific capacity around 195 mAh g −1 at 1 A g −1 with a cycling life of 500 cycles. [24] Herein, we developed a donor-acceptor (D-A) Pz-based conjugated microporous polymer (TzPz) cathode by integrating the electron-donating Pz unit and the electron-withdrawing 2,4,6-triphenyl-1,3,5-triazine (Tz) unit into a polymer chain. Compared with its counterpart polymer BzPz produced from 1,3,5-triphenylbenzene (Bz) and Pz, the TzPz cathode with D-A molecular structure shows a higher conjugation degree and a narrower band gap, which are beneficial for the electron transportation along the polymer chains in TzPz during the charge/discharge process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the p-DPPZ delivered higher capacity retention of 81.7% after 1000 cycles (Figure 21e). [201][202][203] In addition, the 1-/2-positions of phenazine and phenyl units are usually modified with different functionalities to adjust the redox voltage. The redox plateaus of -OMe substituted polymer decreased by 0.1-0.2 V and that of the -CN substituted polymer increased by 0.2 V. [204] Besides, the triphenylamine, [205] 2,4,6-triphenyl-1,3,5-triazine (Tz), 1,3,5-triphenylbenzene (Bz) [206] were utilized to replace the phenyl in p-DPPZ, forming highly-crosslinked structures.…”
Section: Imine Polymersmentioning
confidence: 99%